Four pottery assemblages buried by late antique eruptions of Vesuvius - De Simone, Girolamo Ferdinando; Castaldo, Vincenzo; Sannino, Santa (Rei Cretariae Romanae Fautorum Acta, 2022)
This contribution describes the pottery assemblage from the Roman villa with baths in Pollena Trocchia (Mt. Vesuvius), whose importance resides mostly in its stratigraphy: it was built on top of the AD 79 ashes and buried by volcanic debris in AD 472 and 512, providing sharp chronological markers. After a brief discussion on the exact chronology of the late antique eruptions of Vesuvius, a contextual analysis of the deposits from four rooms of the baths is provided. A thorough description of the pottery assemblages, which are presented by context, classes, and typology, follows. Overall the analysis of the potsherds confirms the hypothesis that, during the last phase before the AD 472 eruption, the baths were abandoned and used as dumping area, while on a macroscopic level the assemblage seems pretty consistent with others from Naples in the third quarter of the 5th century AD.